STRATEGI PEMBERDAYAAN KELOMPOK MASYARAKAT PENGAWAS UPAYA PELESTARIAN MANGROVE DI KABUPATEN BENGKALIS (Jurnal Kajian Lingkungan, 2014)
Conditions along the coastal mangrove Indonesia have shown significant damage, particularly the District Bantan. However, there are people who care about the benefits and functions of mangrove ecosystems. This caring community groups joined in a container called a Kelompok Masyarakat Pengawas (Pokmaswas). One such group is the Persatuan Nelayan Jalan Sejahtera (PNJS) Jangkang Village. This study aims to Develop a strategy to realize the empowerment Pokmaswas mangrove preservation. This study was conducted in January-April 2014 in Jangkang Village. To obtain data on mangrove management conducted an observational study in mangrove forests, while to obtain socio-economic data conducted by distributing questionnaires fishermen and comes with doing focus Group Discussion (FGD). After that is done to get the swot analysis of the community empowerment strategy. Research shows that the condition of mangroves in the Village Jangkang in good condition with density64.691.36/ha. Mangroves are the most dominating species of Rhizophoraapiculata. From the results of swot analysis conducted found 4 empowerment strategy manager mangrove communities that develop ecotourism in the region to manage the group, Improved skills-based mangrove communities make products, Implement training and development of mangrove utilization Lestari.Keywords: Mangrove, Pokmaswas, Strategy, Community Empowerment, PNJS